Budaya Organisasi Mempengaruhi Proses Perpolitikan di Universitas Islam Negeri Sumatera Utara - Muhammad Siddiq Rifa’i; Wildan Ansori Hasibuan; Shelsy Agifurnama; Abdan Mamlukan Almalik Almulk; Khairul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Political education is one of the most important methods to prepare the younger generation to not only understand their rights and obligations in politics, but also have self-confidence in political parties. This study was conducted at the State Islamic University of North Sumatra (UINSU) to identify organizational practices in providing political education to students. Data collection was carried out using qualitative methods and case study designs, with 20 respondents from the organizational community, as well as observation and document analysis. The findings show that student organizations make a significant contribution to increasing student participation in politics through various activities such as leadership training and public discussions. However, issues such as active participation and students' understanding of politics are the main focus. Therefore, political education through student organizations must continue to be developed in order to better prepare students to become critical thinkers with integrity in everyday life.